2011
DOI: 10.1590/s0102-311x2011000600006
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida e fatores de risco para mortalidade neonatal em uma coorte de nascidos vivos de muito baixo peso ao nascer, na Região Sul do Município de São Paulo, Brasil

Abstract: Estudos populacionais sobre mortalidade neonatal de nascimentos de muito baixo peso ao nascer contribuem para identificar sua complexa rede de fatores de risco. Foi estudada uma coorte de 213 recém-nascidos com peso inferior a 1.500g (112 óbitos neonatais e 101 sobreviventes) na Região Sul do Município de São Paulo, Brasil, em 2000/2001. Foram realizadas entrevistas domiciliares e obtidos dados de prontuários hospitalares. Foi realizada análise de sobrevida e empregada regressão múltipla de Cox. A elevada mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
17

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
1
16
1
17
Order By: Relevance
“…In fact, absent or inadequate monitoring of pregnancy has been showing to be a risk factor for neonatal mortality (2)(3) . Association between number of prenatal consultations and neonatal mortality was also observed in a study with a population of live births, nonexclusive of low weight, which we observe a 3.78 times greater risk of death in newborns of mothers with less than seven consultations during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, absent or inadequate monitoring of pregnancy has been showing to be a risk factor for neonatal mortality (2)(3) . Association between number of prenatal consultations and neonatal mortality was also observed in a study with a population of live births, nonexclusive of low weight, which we observe a 3.78 times greater risk of death in newborns of mothers with less than seven consultations during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…This group represents more than half of neonatal deaths, especially those who are born with extremely low birth weight (3) , confirmed by numerous studies that addresses low birth weight as one of the main factors associated with increased likelihood of death in the neonatal period (2,(6)(7)(8)(9)(10) .…”
Section: Neonatal Mortality In Infants With Low Birth Weigh Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Some Brazilian studies have shown a greater percentage of deaths in infants whose mothers had vaginal delivery (4,7) , while cesarean section has been considered a protective factor for mortality (4) , especially for premature and low-weight neonates (19) . However, this relationship was not observed in the present study.…”
mentioning
confidence: 99%